Pengaruh loan to deposit ratio (LDR), dan return on equity (ROE) terhadap harga saham pada perusahaan sektor perbankan yang terdaftar di Bursa Efek Indonesia tahun 2022-2024 - Regita Frizchila Inggo; Sonny Pangerapan; Steven J. Tangkuman (Yayasan Widyantara Nawasena Raharja, 2026)
Stock prices reflect firm value and serve as a key reference for investors’ decision-making in the capital market. This study examines the effect of the Loan to Deposit Ratio (LDR) and Return on Equity (ROE) on the stock prices of banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using a quantitative approach, the study applies purposive sampling to obtain 41 banking firms, resulting in 123 firm-year observations. Multiple linear regression analysis is employed using IBM SPSS 27. The results indicate that LDR has a positive and statistically significant effect on stock prices, suggesting that banks’ effectiveness in channeling third-party funds into credit acts as a positive signal to investors regarding liquidity management and income generation. Likewise, ROE shows a positive and significant influence on stock prices, indicating that higher profitability enhances investor confidence in management’s ability to generate returns from shareholders’ equity. These findings support signaling theory, which posits that financial performance indicators convey important information to the market and influence investor behavior. The study implies that liquidity and profitability ratios are fundamental considerations for investors in valuing banking stocks and for bank management in maintaining market credibility.